The sweet taste signalling pathways in the oral cavity and the gastrointestinal tract affect human appetite and food intake: a review. (17th February 2019) - Han, Pengfei; Bagenna, Bagenna; Fu, Minghai
Abstract: Sweet taste is associated with food reward and energy source in the form of carbohydrate. Excessive sweet consumption is blamed for the prevalence of obesity. However, evidence for the potential of sweet taste to influence food intake and bodyweight regulation in humans remains unclear. The purpose of this review was to examine the physiological responses relevant to sweet taste mechanisms and the impact on appetite control. The literature was examined for studies that assessed the effects of non-nutritive sweeteners and natural sugars on hormonal secretions and neural activations via oral and gastrointestinal pathways. The findings indicated that a network of sweet taste signalling pathways in the oral cavity and the gut seem to mediate hormonal responses and some metabolism differences in neural circus that orchestrating the hunger-satiety cycle. Individual variations of sweet taste perception which is modulated by hormonal and genetic factors have been associated with dietary nutrient and sugar consumption.